دراسة قياسية لأثر تقلبات سعر صرف الدينار الجزائري على النمو الاقتصادي باستخدام نموذجي Fmols و Ecm خلال الفترة (1980-2020) - مسعودي, زكرياء; عزي, خليفة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة لمعالجة العلاقة بين تقلبات سعر الصرف والنمو الاقتصادي في الجزائر خلال الفترة (1980-2020)، وقد تم استخدام نموذج المربعات الصغرى المصححة كلياً (FMOLS) لاستخراج العلاقات طويلة الأجل بين متغيرات الدراسة، ونموذج تصحيح الخطأ (ECM) لاستخراج العلاقات في الأجل القصير. وخلصت الدراسة إلى أن تقلبات سعر صرف الدينار الجزائري تؤثر سلبا على النمو الاقتصادي، سواء في الأجل الطويل أو الأجل القصير، لذلك على السلطات النقدية في الجزائر العمل على استقرار سعر الصرف، الأمر الذي سوف يؤدي إلى جذب الاستثمار الأجنبي وزيادة التجارة الخارجية واستقرار المؤشرات الاقتصادية الكلية، وبالتالي تحقيق النمو الاقتصادي. This study aims to address the relationship between exchange rate volatility and economic growth in Algeria during the period (1980-2020), and the method of least squares completely corrected (FMOLS) was used to extract the long-term relationships between the study variables, and the error correction model (ECM) to extract the relationships in the short-term. The study concluded that fluctuations in the Algerian dinar exchange rate negatively affect economic growth, whether in the long or short term, so the monetary authorities in Algeria should work on stabilizing the exchange rate, which will lead to attracting foreign investment, increasing .foreign trade and stabilizing macroeconomic indicators, and then achieving economic growth
Keywords: تقلبات سعر الصرف، نمو اقتصادي، الدينار الجزائري، التكامل المشترك، نموذج FMOLS ; Exchange rate volatility, Economic growth, Algerian dinar, Cointegration, FMOLS model